The effect of vegetable oils and the fish oil on the fatty acid profile in egg yolks - Kralik, Gordana (Array, 2020)
The paper presents the results of a research in the use of flaxseed (LO) and rapeseed oil (RO) in a combination with fish oil (FO) in the feeding of laying hens and the effect on the fatty acid profile of egg yolks (∑n-3 PUFA and ∑n-6/∑n-3 PUFA ratio). Nutritional treatments were as follows: C1, C2 = control (5% soybean oil SO), E1 = 1.5% LO+3.5% FO, E2 = 3.5% LO+1.5% FO, E3 = 1.5% RO+3.5% FO, E4 = 3.5% RO+1.5% FO. Feed mixtures for the laying hens were balanced on the basis of a 17% crude protein and 11.5 MJ/kg ME, and the n-6/n-3 PUFA ratio in the mixtures was as follows: C1 13.64, C2 13.10, E1 2.63, E2 1.53, E3 4.84 and E4 6.21. The combination of the flaxseed oil and fish oil in the feed affected the n-6/n-3 PUFA ratio, making it narrower when compared to the combination of rapeseed oil and the fish oil. The control feed C1 and C2 contained only ALA 3.12 and 4.08%, being without the EPA and DHA fatty acids. The analysis of the fatty acid profiles in egg yolks demonstrated that the eggs contained 1.16 and 1.26% of DHA in addition to ALA, which means that, although in the small amounts, the DHA was synthesized and deposited in the eggs by the laying hens. The following proportions of n-3 PUFAs were found in the eggs of the experimental groups: E1 6.51%, E2 8.30%, E3 5.17%, and E4 3.54%. The n-6/n-3 PUFA ratio in egg yolks decreased from 9.67 and 11.85 (control groups) to 3.08 and 2.57, respectively, for the flaxseed and fish oil treatments and 4.25 and 6.95 for the rapeseed and fish oil treatment. The studies have demonstrated a more efficient deposition of the n-3 PUFAs in the yolks of the E1 and E2 groups, although the ALA was most abundantly present in the total n-3 PUFAs.